Using Onomatopoeia in Comic to Improve Vocabulary - Tiara Eliza (Global Expert: Jurnal Bahasa dan Sastra, 2019)
AbstractIn the field of second language teaching, vocabulary has been one of the most neglected areas in the classroom. That is why there are many students who lacks of vocabulary will find difficulties in language learning process. They will find difficulties in communication. Therefore vocabulary has an important role in communication process both spoken and written. Vocabulary is needed to support a success communication. This study was meant to find out how to improve vocabulary by using onomatopoeic expression in comic and to describe some challenges in using comic as a media of teaching and learning process. This study used a qualitative descriptive analysis. The participants were taken from the students in private classes. The research data is collected by using test (test after the first treatment and test after the second treatment) and by observation for collecting data on the students’ motivation in improving vocabulary mastery using onomatopoeic expression. The data were analyzed by using the descriptive analysis. The result showed that in the first cycle, the students’ average was 65.8, then, on the second treatment, the students’ average increase to be 75.9. It can conclude that teaching vocabulary by using onomatopoeic expression in comic can be used as media to improve students’ vocabulary ability.Keyword : Onomatopoeia, Vocabulary, ComicAbstrakDi dalam bidang pengajaran bahasa kedua, kosakata menjadi salah satu hal yang diabaikan didalam kelas. Oleh karena itu wajar jika banya siswa-siswa yang memiliki keterbatasan kosakata akan menemukan kesulitan dalam proses mempelajari bahasa kedua. Mereka akan menemukan kesulitan dalam berkomunikasi. Oleh karena itu, kosakata memegang peranan penting dalam proses berkomunikasi antara satu dengan yang lain baik secara lisan maupun tulisan. Dalam hal ini kosakata sangat diperlukan untuk menunjang suksesnya proses berkomunikasi. Penelitian ini bertujuan untuk menjelaskan bagaimana cara meningkatkan dan memperkaya kosakata dengan menggunakan kata-kata onomatopea atau beberapa bentuk ekspresi onomatopea yang terdapat didalam komik dan penelitian ini juga dimaksudkan untuk melihat serta meninjau beberapa tantangan yang akan dihadapi ketika menggunakan komik didalam proses pembelajaran bahasa kedua. Penelitian ini adalah penelitian yang bersifat analisis deskriptif kualitatif. Data dalam penelitian ini diambil dari beberapa kelas privat. Adapun bentuk pengumpulan data yang digunakan  adalah dengan menyelenggarakan beberapa tes dan observasi untuk melihat bagaimana kata dan ekspresi onomatopea yang terdapat di dalam komik dapat memberikan motivasi kepada para siswa dalam meningkatkan kemampuan penguasaan kosakata. Hasil penelitian ini menunjukan bahwa terdapat peningkatan perolehan nilai rata-rata siswa dari 65.8 menjadi 75.9. Maka dapat disimpulkan bahwa penggunaan kata-kata onomatopea didalam komik mampu meningkatkan dan memperkaya kosakata.Kata kunci : Onomatopea, Kosakata, Komik